2018
DOI: 10.1038/s41467-017-02577-y
|View full text |Cite
|
Sign up to set email alerts
|

Multi-day rhythms modulate seizure risk in epilepsy

Abstract: Epilepsy is defined by the seemingly random occurrence of spontaneous seizures. The ability to anticipate seizures would enable preventative treatment strategies. A central but unresolved question concerns the relationship of seizure timing to fluctuating rates of interictal epileptiform discharges (here termed interictal epileptiform activity, IEA), a marker of brain irritability observed between seizures by electroencephalography (EEG). Here, in 37 subjects with an implanted brain stimulation device that det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

42
596
10
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 443 publications
(651 citation statements)
references
References 47 publications
42
596
10
3
Order By: Relevance
“…This is well in line with the findings published by Baud et al 17 Qualitatively, the objective seizure count provided information on participants' response to changes in AEDs that would not have been revealed from the seizure diaries. We have shown that home monitoring for approximately 3 months is feasible ID Onset zone Semiology a without major adverse events or significant impact on activities of daily living.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is well in line with the findings published by Baud et al 17 Qualitatively, the objective seizure count provided information on participants' response to changes in AEDs that would not have been revealed from the seizure diaries. We have shown that home monitoring for approximately 3 months is feasible ID Onset zone Semiology a without major adverse events or significant impact on activities of daily living.…”
Section: Discussionsupporting
confidence: 89%
“…Several other seizure-detection devices have appeared within the last decade, some employing EEG 2,10,17,21,22 and some employing other technologies, such as EMG/accelerometry, 23,24 heart rate variability, 25 electrodermal activity, or a combination of these. Several other seizure-detection devices have appeared within the last decade, some employing EEG 2,10,17,21,22 and some employing other technologies, such as EMG/accelerometry, 23,24 heart rate variability, 25 electrodermal activity, or a combination of these.…”
Section: Discussionmentioning
confidence: 99%
“…First, EEG and ECoG recordings show that many partial and generalized seizures initiate with a single or recurrent spikes . Second, long‐term recordings reveal the frequency of interictal spikes tend to gradually increase prior to seizures . Third, single cell intracellular voltage recordings show that paroxysmal depolarization shifts underlie both spikes and onset of seizures .…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, algorithms that directly account for known seizure triggers, such as sleep‐wake rhythms, as well as novel measurement approaches may offer alternative routes to performance gains . In addition, recent work looking at long‐term rhythms holds significant promise for seizure forecasting, could be applied in the machine learning context, and suggests that the performance limits seen here may not be tied to potential limits imposed by the physiologic processes underlying seizure occurrence.…”
Section: Discussionmentioning
confidence: 99%